2017
DOI: 10.1159/000481408
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Nutritional Optimization for Crohn’s Disease Patients Can Improve Surgical Outcome

Abstract: Background: Preoperative preparation of patients with Crohn’s disease is challenging and there are no specific guidelines regarding nutritional support. The aim of this study was to assess whether preoperative nutritional support influenced the postoperative outcome. Methods: A retrospective, cohort study including all Crohn’s disease patients who underwent abdominal surgery between 2008 and 2014 was conducted. Patients’ characteristics and clinical and surgical data were recorded and analyzed. Results: Eighty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…As shown in our study, 77.5% of hypoalbuminemic patients had preoperative NRS score ≥ 3, which indicated that malnutrition might be an important contributor to the occurrence of hypoalbuminemia. Until now, several studies have demonstrated significantly better results in overall and infectious complications in patients undergoing preoperative nutritional therapy [3133]. However, data on the association between nutritional support and postoperative AKI were limited.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in our study, 77.5% of hypoalbuminemic patients had preoperative NRS score ≥ 3, which indicated that malnutrition might be an important contributor to the occurrence of hypoalbuminemia. Until now, several studies have demonstrated significantly better results in overall and infectious complications in patients undergoing preoperative nutritional therapy [3133]. However, data on the association between nutritional support and postoperative AKI were limited.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the optimization of the nutritional status before surgery (with either enteral or parenteral support) reduces post-operative intra-abdominal septic complications and the need for a temporary diverting stoma (112). More recently a retrospective, cohort study including all CD patients who underwent abdominal surgery showed that nutritional support can minimize post-operative complications in IBD patients with low albumin levels (113).…”
Section: Immunonutrition As a Novel Ibd Therapeutic Approach?mentioning
confidence: 99%
“…This malnutrition could worsen due to diverse surgical interventions that are necessary for emerging situations or when the medical treatment fails [54]. Therefore, the nutritional support should be carefully chosen during the treatment and before the surgery, based on a plan that is customized according to the patient [55]. Some authors declare that PN results in an increase in BMI, helping to correct the individual's malnutrition [23,56].…”
Section: Discussionmentioning
confidence: 99%